2017
DOI: 10.1002/hipo.22743
|View full text |Cite
|
Sign up to set email alerts
|

Theta‐paced flickering between place‐cell maps in the hippocampus: A model based on short‐term synaptic plasticity

Abstract: Hippocampal place cells represent different environments with distinct neural activity patterns. Following an abrupt switch between two familiar configurations of visual cues defining two environments, the hippocampal neural activity pattern switches almost immediately to the corresponding representation. Surprisingly, during a transient period following the switch to the new environment, occasional fast transitions between the two activity patterns (flickering) were observed (Jezek, Henriksen, Treves, Moser, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
17
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 66 publications
4
17
2
Order By: Relevance
“…5B). This finding is at first sight in disagreement with the exponential decay of the flickering frequency reported in [27,38]. However, the latter was obtained as a result of an averaging over many teleportation events.…”
Section: Discussioncontrasting
confidence: 84%
See 2 more Smart Citations
“…5B). This finding is at first sight in disagreement with the exponential decay of the flickering frequency reported in [27,38]. However, the latter was obtained as a result of an averaging over many teleportation events.…”
Section: Discussioncontrasting
confidence: 84%
“…The present model reproduces accurately all the observed flickering properties, without any need for a post-learning short-term plasticity of the CA3 network hypothetized in [38]. In particular, our model predicts that the flickering frequency is independent from the time spent after the teleportation event in the conflicting phase (Fig.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…spontaneously) and under naturalistic conditions (here self-paced, goal-directed navigation); these dynamics were moreover seen in the absence of overtly deliberative behaviors such as directed head scans (vicarious trial-and-error 12 ). Most immediately, these various properties suggest revised or new models of network-level theta dynamics [61][62][63][64][65][66] .…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that the conflicting signals for local features such as orientation (Bonds, 1989;Sillito, 1975), motion direction (Mikami et al, 1986;Snowden et al, 1991), and edge assignment (Kogo & van Ee, 2015;Zhou et al, 2000) compete with each other through such mutual inhibition circuits. This mutual inhibition circuit has been implemented in computer models to explain bistable perception (Laing & Chow, 2002;Lankheet, 2006;Matsuoka, 1984;Mueller, 1990;Noest et al, 2007;Shpiro et al, 2009;Wilson et al, 2000;Wilson, 1999), object recognition (Masquelier et al, 2009), decision making (Heuer, 1987;Machens et al, 2005;Usher & McClelland, 2001), and place cell field generation (Mark et al, 2017). It has also been suggested that these circuits underlie mechanisms such as larger scale neural interactions and feedback systems (Beck & Kastner, 2005;Lee et al, 1999;Wang et al, 2013) that establish a globally coherent percept.…”
Section: Introductionmentioning
confidence: 99%